The contribution of iron deficiency to the risk of peripartum transfusion: a retrospective case control study - H. VanderMeulen (BMC Pregnancy and Childbirth, 2020)
Abstract Background Iron deficiency in pregnancy is associated with inferior maternal and fetal outcomes. Postpartum depression, prematurity, intrauterine growth restriction, impaired childhood cognition and transfusion are all sequelae of maternal iron deficiency anemia. Transfusion to women of childbearing age has important consequences including increasing the risk of hemolytic disease of the fetus and newborn with future pregnancies. The relative contribution of iron deficiency to transfusion rates in the peripartum period is unknown. This study aimed to identify the prevalence of iron deficiency and anemia in pregnant women that received peripartum transfusions relative to age-matched non-transfused controls. Methods We performed a retrospective case-control study of all women that were transfused in the peripartum period from January, 2014 to July, 2018. Cases were compared to the next age matched control to deliver at our institution. The primary objective was to determine the proportion of patients with iron deficiency in pregnancy or anemia in pregnancy in cases and controls. Charts were reviewed for predisposing risk factors for iron deficiency, laboratory measures of iron deficiency and anemia, iron supplementation history and maternal and fetal outcomes. Factors associated with peripartum transfusion were analyzed using a multivariate logistic regression. Results 169 of 18, 294 (0.9%) women were transfused in the peripartum period and 64 (44%) of those transfused received 1 unit. Iron deficiency or anemia were present in 103 (71%) transfused women and 74 (51%) control women in pregnancy (OR 2.34, 95% CI: 3.7–18.0). Multivariate analysis identified social work involvement (adjusted OR 4.1, 95% CI: 1.8–10.1), intravenous iron supplementation in pregnancy (adjusted OR 3.8, 95% CI: 1.2–17.4) and delivery by unscheduled cesarean section (adjusted OR 2.8, 95% CI: 1.3–6.2) as significant predictors of peripartum transfusion. Conclusions Pregnant women being followed by a social worker, receiving intravenous iron supplementation in pregnancy or who deliver by unscheduled cesarean section are more likely to receive a red blood cell transfusion. Women with iron deficiency or anemia in pregnancy are at increased risk of peripartum blood transfusions and warrant early and rigorous iron supplementation.